Myocardial Recovery versus Myocardial Regeneration: Mechanisms and Therapeutic Modulation - John P. Cooke; Keith A. Youker; Li Lai (Methodist DeBakey Cardiovascular Journal)
Myocardial recovery is characterized by a return toward normal structure and function of the heart after an injury. Mechanisms of myocardial recovery include restoration and/or adaptation of myocyte structure and function, mitochondrial activity and number, metabolic homeostasis, electrophysiological stability, extracellular matrix remodeling, and myocardial perfusion. Myocardial regeneration is an element of myocardial recovery that involves the generation of new myocardial tissue, a process which is limited in adult humans but may be therapeutically augmented. Understanding the mechanisms of myocardial recovery and myocardial regeneration will lead to novel therapies for heart failure.